IMPLEMENTASI KEBIJAKAN STANDAR NASIONAL PERPUSTAKAAN PERGURUAN TINGGI: DI PERPUSTAKAAN UNIVERSITAS NEGERI MALANG - Santoso Haryono, Bambang; Yudi Cahyono, Teguh (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2020)
The purpose of this study was to determine and describe the implementation of the National Standards for Higher Education Libraries (SNP-PT) that have been carried out by UM Library. The method used in this research is a combination of qualitative-quantitative, by observing and conducting interviews related to the implementation of the SNP-PT at the UM Library as well as using data in the form of numbers on the performance indicators of each component of the national standard. Achievement of collection indicators, UM Library have implemented 12 out of 14 collection standards for higher education libraries (85,7%). Achievement of facilities and infrastructure indicators, UM Library have implemented 18 of 19 standard facilities and infrastructure for higher education libraries (94,7%). Achievement of service indicators, UM Library have implemented 5 out of 5 service standards for higher education libraries (100%). Achievement of staff indicators, UM Library have implemented 8 out of 10 staff standards for higher education libraries (80%). Achievement of standard administration indicators, UM Library has implemented 6 out of 7 higher education library administration standards (85,7%). Achievement of management indicators, UM Library have implemented 12 out of 12 management standards for higher education libraries (100%). This research shows that the implementation of the SNP-PT policy has been “good” done in UM Library with an average achievement 91,01% of the standards that have been set.